Microdetermination of 4-chlorophenol and 5-chloro-8-Hydroxyquinoline with bromine Chloride and Its Application to Pharmaceutical Preparations - Seetharamappa, J. (Asian Journal of Chemistry, 2010)
A simple titrimetric method for the microdetermination of 4-chlorophenol and 5-chloro-8-hydroxyquinoline in acetic acid medium is described. The proposed method can be successfully applied for the assay of methyldopa and halquinol in pharmaceutical preparations.